(3GdJabjg aj TQM GdJfHjgs - (3CHh YHO Gdgd eMeO Hf YHO Gddg Hf CHi HcQ GdUQOai GdQjeis; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
(3jHOC HHGH GdUOGb s
(3BNQgG (B:s
(3aEPG fhGg HbdH dGjbHd ai GdMce hjOjf ai GdHGWf EdG ai GdESJKfGA s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfGhjf HGdMeQIs
(3hYdi MhGTjgG JYdjbGJ hJUMjMGJ s
(3hcJHJ HQSe NRGfI GdEeGe ESeGYjd Hf GdYHGS Hf Ydi Hf OGhO Hf jhSa Hf QShd GdZSGfi s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3Gdabg GdTGaYjs